Effect Of Loading Vehicle On Strain Value And Load Repetition Using Mechanistic Method - Zulfhazli Zulfhazli; Fasdarsyah Fasdarsyah; Hendry Hendry (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
The main component in the road's construction is its pavement. The pavement is used to protect subgrade soil as well as prevent it from the overload of the strain due to a big number of loading repetitions. It also used to lengthen the durability of the roads, therefor it minimizes the need of renovations. In this research, we use mechanistic approach namely KENPAVE program that analyze the response of the structure of each pavement layers. The objective of this program is to response to the result of pavement's structure which is horizontal and vertical tensile of strain, under both surface layer and upper subgrade layer. The following step is the calculation of loading repetition's value in the failure, in doing so, rutting damages are taken into account. Parameter study in this research is to vary vehicle's loading capacity, which is one of the mechanistic method parameter. Splitting variation of the vehicle's loading capacity into five variations from standard variation 265,5 KPa to 365,5 KPa, 465,5 KPa, 565,5 KPa, and 665,5 KPa. Next, the research will be inputting values to the KENPAVE program to collect strain's values and calculate loading repetition's values. The result found from through the research is that the more loading variations, the higher strain into the road pavement's structure, and the less loading variation, the lower strain take place. Strain values are also influenced by loading repetitions' values inversely proportional. The higher strain's value, the fewer sums of the loading repetitions.